Academic integrity in the use of artificial intelligence in university students: Review article - Rufino Gabriel, Margarita Mercedes; Rueda Ñopo, Melisa Isabel; Gabriel Rojas, Fanny Giovana; Ponte Córdova, Santos (LACCEI, 2025)
The objective of the research is to analyze academic integrity in the use of artificial intelligence in university students, for which the scientific literature from the Scopus database was reviewed. For the research, 600 scientific articles were initially evaluated. The PICOT methodology was used to determine the search parameters and research questions, and PRISMA was also used for the ideal selection of articles based on inclusion and exclusion criteria, obtaining in a first filtering 123 articles and in a second, 95 articles, which were reviewed in their entirety. Regarding the results, students perceive the impact of AI on academic integrity both positively and negatively. Likewise, there are various problems that arise such as: plagiarism, dependency, loss of critical skills, lack of AI detection, lack of clear standards, etc. Furthermore, 83.3% consider that AI favors integrity, but is also a threat, so it is necessary to establish clear guidelines based on a culture and ethical training. Keywords-- Artificial intelligence, academic integrity, higher education, ethics.